2012
DOI: 10.1007/s00122-012-2000-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic regions involved in resistance against Sclerotinia sclerotiorum from wild Brassica oleracea

Abstract: The lack of resistant source has greatly restrained resistance breeding of rapeseed (Brassica napus, AACC) against Sclerotinia sclerotiorum which causes severe yield losses in rapeseed production all over the world. Recently, several wild Brassica oleracea accessions (CC) with high level of resistance have been identified (Mei et al. in Euphytica 177:393-400, 2011), bringing a new hope to improve Sclerotinia resistance of rapeseed. To map quantitative trait loci (QTL) for Sclerotinia resistance from wild B. ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 30 publications
3
79
1
1
Order By: Relevance
“…The fact that QTLs for the resistance on C6 can be repeatedly mapped suggests the importance of genetic components from B. oleracea (C-genome) for S. sclerotiorum . This is also consistent with recent studies which found several QTLs in C-genome [47], [48]. Further fine mapping and eventually cloning of SRC6 identified in this research will offer novel information for understanding the resistance mechanism and provide valuable resources for Sclerotinia -resistant breeding, since immune or highly resistant germplasms are not available in B. napus and its close relatives.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that QTLs for the resistance on C6 can be repeatedly mapped suggests the importance of genetic components from B. oleracea (C-genome) for S. sclerotiorum . This is also consistent with recent studies which found several QTLs in C-genome [47], [48]. Further fine mapping and eventually cloning of SRC6 identified in this research will offer novel information for understanding the resistance mechanism and provide valuable resources for Sclerotinia -resistant breeding, since immune or highly resistant germplasms are not available in B. napus and its close relatives.…”
Section: Discussionsupporting
confidence: 91%
“…sclerotiorum [2], B . napus ‘Charlton’ cultivar [34, 35] and Brassica oleracea [37] as well as the hexaploid B . napus (AACCCC), derived from crosses between ‘Zhongshuang 9’ and B .…”
Section: Discussionmentioning
confidence: 99%
“…Further, Zhang et al (2011) demonstrated QTL linked to SR resistance in B. napus, either at seedling or adult plant stages, and while QTL qSRS1, qSRS9, qSRM3 and qSRM9 had a positive effect towards SR resistance, only qSRS9 at the seedling stage and qSRM9 at the adult stage were at the same position on linkage group N9. Mei et al (2013) also concluded that the genetic control of leaf and stem resistance are probably different. The involvement of so many QTL suggests that there may be diverse mechanisms by which brassicas resist invasion by S. sclerotiorum, and the results of our study support the emerging certainty for different mechanisms for resistance in leaves and stems.…”
Section: Natural Ascospore Leaf Infection and Comparison With Stem Inmentioning
confidence: 99%